Pengaruh Electronic Word of Mouth dan Influencer Marketing terhadap Keputusan Menginap di Adiwana Warnakali Resort Nusa Penida - Negara, I Dewa Agung Anom Segening Putra; Sudiksa, I Nyoman; Pinaria, Ni Wayan Chintia (Journal of Hospitality Accommodation Management (JHAM), 2024)
The aim of this research is to analyze the influence of electronic word of mouth and influencer marketing on the decision to stay at Adiwana Warnakali Resort. The number of samples in this study was 100 respondents using the Slovin formula. Data collection was carried out by distributing questionnaires to guests who had stayed at Adiwana Warnakali Resort. The data analysis techniques used in this research are the classical assumption test, multiple linear regression analysis, t-test, F test, and coefficient of determination with data analysis tools using the SPSS version 26 program. The results of this research show that electronic word of mouth has a positive effect and significant to the decision to stay overnight partially with the Sig value. 0.000 < 0.05, influencer marketing has a positive and significant effect on the decision to stay overnight partially with a Sig value. 0.000 < 0.05 and electronic word of mouth and influencer marketing have a positive and significant effect on the decision to stay overnight simultaneously with a Sig value. 0.000 < 0.05. Based on the results of this research, the advice that can be given is that Adiwana Warnakali Resort is expected to be able to manage online reviews well by providing feedback or replying to consumer reviews and conducting research on new trends so that the content that will be uploaded by influencer marketing is interesting and increases the decision to stay overnight at Adiwana Warnakali Resort.